Prediction of sonic velocities from other borehole data: An example from the Kevitsa mine site, northern Finland - Kieu, D.; Kepic, Anton; Kitzig, M. (Wiley-Blackwell, 2018)
P-wave and S-wave velocities are vital parameters for the processing of seismic data and may be useful for geotechnical studies used in mine planning if such data were collected more often. Seismic velocity data from boreholes increase the robustness and accuracy of the images obtained by relatively costly seismic surface reflection surveys. However, sonic logs are rarely acquired in boreholes in-and-near base metal and precious metal mineral deposits until a seismic survey is planned, and only a few new holes are typically logged because the many hundreds of holes previously drilled are no longer accessible. If there are any pre-existing petrophysical log data, then the data are likely to consist of density, magnetic susceptibility, resistivity and natural gamma logs. Thus, it would be of great benefit to be able to predict the velocities from other data that is more readily available. In this work, we utilize fuzzy c-means clustering to build a “fuzzy” relationship between sonic velocities and other petrophysical borehole data to predict P-wave and S-wave velocity. If boreholes with sonic data intersect most of the important geological units in the area of interest, then the cluster model developed may be applied to other boreholes that do not have sonic data, but do have other petrophysical data to be used for predicting the sonic logs. These predicted sonic logs may then be used to create a three-dimensional volume of velocity with greater detail than would otherwise be created by the interpolation of measured sonic data from sparsely located holes. Our methodology was tested on a dataset from the Kevitsa Ni-Cu-PGE deposit in northern Finland. The dataset includes five boreholes with wireline logs of P-wave velocity, S-wave velocity, density, natural gamma, magnetic susceptibility and resistivity that were used for cluster analysis. The best combination of input data for the training section was chosen by trial and error, but differences in the misfit between the various training datasets were not particularly significant. Our results show that the fuzzy c-means method can predict sonic velocities from other borehole data very well, and the fuzzy c-means method works better than using multiple linear-regression fitting. The predicted P-wave velocity data are of sufficient quality to robustly add low-frequency information for seismic impedance inversion and should provide better velocity models for accurate depth conversion of seismic reflection data.